Serotonin Transporter Genotype Affects Serotonin 5-HT(1A) Binding in Primates - Christian, Bradley T. (Society for Neuroscience, 2013)
Disruption of the serotonin system has been implicated in anxiety and depression and a related genetic variation has been identified that may predispose individuals for these illnesses. The relationship of a functional variation of the serotonin transporter promoter gene (5-HTTLPR) on serotonin transporter binding using in vivo imaging techniques have yielded inconsistent findings when comparing variants for short (s) and long (l) alleles. However, a significant 5-HTTLPR effect on receptor binding at the 5-HT(1A) receptor site has been reported in humans, suggesting the 5-HTTLPR polymorphism may play a role in serotonin (5-HT) function. Rhesus monkeys possess a 5-HTTLPR length polymorphism similar to humans and serve as an excellent model for studying the effects of this orthologous genetic variation on behaviors and neurochemical functions related to the 5-HT system. In this study, PET imaging of [(18)F]mefway was performed on 58 rhesus monkeys (33 l/l, 25 s-carriers) to examine the relation between 5-HT(1A) receptor-specific binding and 5-HTTLPR genotypes. Significantly lower 5-HT(1A) binding was found in s-carrier subjects throughout both cortical brain regions and the raphe nuclei. These results demonstrate that the underlying 5-HT neurochemical system is influenced by this functional polymorphism and illustrate the strong potential for extending the nonhuman primate model into investigating the role of this genetic variant on behavior and gene–environment interactions.